America's death penalty : between past and present - Garland, David; McGowen, Randall, 1948-; Meranze, Michael (New York : New York University Press, 2016)
'America's Death Penalty' examines the historical and theoretical assumptions that have underpinned the discussion of capital punishment in the United States.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on February 1, 2016).
Keywords: Capital punishment -- United States; True Crime; United States of America, USA; History of the Americas; Social services & welfare, criminology; Crime & criminology; Penology & punishment